HUBUNGAN PERAN PENYULUH PERTANIAN LAPANG DENGAN TINGKAT PARTISIPASI ANGGOTA KELOMPOK DALAM INDUSTRI PENGOLAHAN PANGAN LOKAL - Eka Nopitasari; Suherman Suherman; Gugun Gunawan (JURNAL AGRIBISNIS TERPADU, 2017)
The purpose of this study is to know the role of agricultural extension officers in the fields of food processing industry, to know the level of participation of the members of the Group of women farmers in food processing industry, the relationship of agricultural extension officers role with the participation of members in local food processing. The type of this research is descriptive analysis using survey method and quantitative approach. The determination of the location purposively with consideration that Sidamukti village, Baros district is one of the villages that make the food processing industry. Sample in this research is 33 respondents. Data collection research using questionnaires, measured using likertscale and Rank Spearman. The role of extension officers included into good category. The level of participation of the members of the Group of women farmers in local food processing industry in planning production, participation of members of the group in partnering or collaborating, and the participation of members in the activities of the evaluation of processing, classified into good category, as for the level of participation of the members of the Group of women farmers in foodexecution of production, and processing technology implementation activities included into good enough category. The relationship between the role of agricultural extension officers with the participation of the members of the Group of women farmers in local food processing industry has a direct and significant relationships.